2003
DOI: 10.1001/archinte.163.6.720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1-Year Oral Administration of Dehydroepiandrosterone to 60- to 80-Year-Old Individuals on Muscle Function and Cross-sectional Area

Abstract: The compensation of the deficit of dehydroepiandrosterone during aging using a 50-mg/d dose does not induce beneficial effects on muscle state in healthy subjects. The conditions in which dehydroepiandrosterone could contribute to preserve or improve muscle strength and morphological features still need to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 32 publications
6
63
0
5
Order By: Relevance
“…Treatments lasted from 4 to 52 weeks and the number of patients in each study was relatively small (from 6 to 60 subjects), although most studies used randomized, double-blind designs. One study was performed in a large sample of men and women (n ¼ 280) (138). A total of eight studies indicated no effect of DHEA replacement on plasma lipids.…”
Section: Exogenous Dheamentioning
confidence: 99%
“…Treatments lasted from 4 to 52 weeks and the number of patients in each study was relatively small (from 6 to 60 subjects), although most studies used randomized, double-blind designs. One study was performed in a large sample of men and women (n ¼ 280) (138). A total of eight studies indicated no effect of DHEA replacement on plasma lipids.…”
Section: Exogenous Dheamentioning
confidence: 99%
“…This conclusion is supported by studies of stress related to sepsis and multiple trauma, in which low serum DHEAS was associated with poor survival in these patients (Beishuizen et al, 2002). The fact that DHEA can be readily supplemented (Baulieu et al, 2000) and has no recorded side-effects with long-term use (Percheron et al, 2003) suggests that this hormone may offer a potential intervention therapy to reduced mortality and morbidity associated with stress and trauma (Jarrar et al, 2001). …”
Section: Adrenal Antiglucocorticoids and Immunitymentioning
confidence: 99%
“…In a study of men and women aged 50-65 years, (90) observed that supplementation with 100 mg of DHEA for 6 months increased lean body mass and decreased fat mass in both sexes, but increased muscle strength only moderately and only in men, and increased testosterone levels only in women. In a randomized placebocontrolled trial of 50 mg/day of DHEA supplementation for 1 year to men and women aged 60-80 years, (94) failed to reproduce Morales's results or detect an increase in lean mass, as indicated by measurements of body potassium.…”
Section: Anabolic Interventionsmentioning
confidence: 90%